Finding satisfactory transparency: An empirical study on public transparent displays in a shop context - Kim, H.; Huh, B.K.; Im, S.; Joung, H.Y.; Kwon, G.H.; Park, J.-H. (Conference on Human Factors in Computing Systems - Proceedings, 2015)
This paper focuses on designing an affective user interface for public transparent displays in a shop context. In order to maintain harmonious view and satisfactory experience, the relationship between the information and transparency needs to be considered. Therefore, in this paper, we investigate different levels of transparency for determining their appropriateness with regard to user's proximity. Two user studies show that 25% transparency is more satisfactory in closer proximity while 50% transparency offers more harmonious view in a distant context. Our findings on satisfactory transparency can be applied to a basis of further investigation for public transparent displays, especially in a shop context. Copyright is held by the author/owner(s).